Representasi Budaya Patriarki yang Dialami Perempuan Dalam Film “Yuni” Karya Kamila Andini - Sazali, Hasan; Alfanny, Aulia; Pratama, Rabiulza (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to analyze the representation of patriarchal culture in the ‘Yuni’ film. This study uses a qualitative approach with a semiotic approach. Data collection techniques using documentation and observation. Data collection is done by collecting scenes in the film titled ‘Yuni’ that represent patriarchy culture. The data analysis technique used is John Fiske's semiotics which consists of three levels, namely: the level of reality, the level of representation, and the level of ideology. The result of the research shows that ‘Yuni’ film represents patriarchal culture. The analysis in this study was carried out by paying attention to conversations, facial expressions, the environment, to the cinematography used in the scenes in the ‘Yuni' film. There are findings of patriarchal culture shown in the ‘Yuni’ film, namely: a complete division of labor for women and the double burden received by women, restrictions on movement of women in terms of pursuing higher education, sexual exploitation of women, physical violence perpetrated by men against women, and restrictions on movement of women by educational institutions. Suggestions from this study there are still shortcomings in it, therefore there is a need for further in-depth research and developing topics related to the concept of gender presented in the film titled 'Yuni', the interpretations generated by the researchers in this study can be different. further research is needed, and the community is expected to be able to absorb films as a medium for community learning that gender inequality is still common in society. Keywords : Semiotic, Film, Patriarchy